AN INVESTIGATION IN TO THE STUDENT OPINIONS AND OBSERVATIONS TOWARDS ANIMATION-SUPPORTED INSTRUCTION IN SOCIAL SCIENCES LESSON - Cevizci, Rukiye Nur Yasak; Çelik, Seda Kerimgil (My University, 2023)
This study aims to investigate the student views and observations towards animation-supported instruction in social studies lessons. The study group consisted of 20 2 nd grades in a primary school in the Eğil district of Diyarbakır in the 2018-2019 academic year. The case study design, one of the qualitative research methods, was used in the research. In this qualitative research in which semi-structured interview form, observation form, and outcome evaluation form used as the data collection tools, Content analysis method was used to analyze the data. The results indicated that the students' interest and love for the lessons increased with animation-supported instruction. Moreover, it was concluded that the students found animation-supported education different, interesting, and fun, supporting their permanent learning.
Keywords: Primary school; technology; Animation; social science lesson